2016
DOI: 10.3389/fnana.2015.00167
|View full text |Cite
|
Sign up to set email alerts
|

Reorganization of Basolateral Amygdala-Subiculum Circuitry in Mouse Epilepsy Model

Abstract: In this study, we investigated the reorganized basolateral amygdala (BLA)-subiculum pathway in a status epilepticus (SE) mouse model with epileptic episodes induced by pilocarpine. We have previously observed a dramatic loss of neurons in the CA1–3 fields of the hippocampus in epileptic mice. Herein, we observed a 43–57% reduction in the number of neurons in the BLA of epileptic mice. However, injection of an anterograde tracer, Phaseolus vulgaris leucoagglutinin (PHA-L) into the BLA indicated 25.63% increase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 59 publications
1
3
0
Order By: Relevance
“…Our study also found that the Eyes Task score decreased with an increase in several previous manic episodes, accounting for decreased socio-perception. These findings, together with data from other studies, are indicative that neuronal loss in the brain is associated with many previous episodes rather than early-onset [17][18][19].…”
Section: Discussionsupporting
confidence: 74%
“…Our study also found that the Eyes Task score decreased with an increase in several previous manic episodes, accounting for decreased socio-perception. These findings, together with data from other studies, are indicative that neuronal loss in the brain is associated with many previous episodes rather than early-onset [17][18][19].…”
Section: Discussionsupporting
confidence: 74%
“…After SE, axon sprouting of granule cells would increase recurrent excitation in the dentate gyrus (Tauck and Nadler, 1985), whereas axonal sprouting of CA1 pyramidal cell would increase CA1 to subiculum excitation (Cavazos et al, 2004). Anatomical projections from the basolateral amygdala to ventral subiculum were also increased after pilocarpine SE (Ma et al, 2015). In the hippocampus, kainate-induced SE resulted in loss of inhibitory interneurons in the distal dendritic layer (Cossart et al, 2001), increase in dendritic excitation and spike excitability (Bernard et al, 2004, Wu and Leung, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…was injected to antagonize the peripheral cholinergic response caused by pilocarpine. Behavioral changes were observed, and seizures were evaluated by the Racine score [ 34 ]. Mice with seizures grade IV or V were used in subsequent experiments.…”
Section: Methodsmentioning
confidence: 99%